DFIG virtual inertia control in micro‐grid based on setting trigger condition and ZN method for parameters optimisation. Issue 15 (3rd October 2017) - Fu, Yang; Huang, Lisha; Zhang, Hengyi; Mi, Yang; Zhao, Jingjing; Li, Fangxing
Abstract : The virtual inertia control (VIC) is used to design frequency regulation for a doubly fed induction generator (DFIG). The VIC method can be improved by adding supplementary control loops for inertia response and rotor speed recovery. In this study, certain delay time of the recovery module is replaced by setting a trigger condition to make the speed recover. Then the modified Ziegler–Nichols (ZN) method is used to calculate proportional–integral parameters of the recovery module quickly and accurately. Finally, the VIC method is applied to the micro‐grid switch grid‐connected mode to unplanned island mode. Simulation results demonstrate that the modified VIC method is effective to improve transient stability for the micro‐gird during switching mode.